If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 = -8x + -8 Reorder the terms: 4 + 6x = -8x + -8 Reorder the terms: 4 + 6x = -8 + -8x Solving 4 + 6x = -8 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 4 + 6x + 8x = -8 + -8x + 8x Combine like terms: 6x + 8x = 14x 4 + 14x = -8 + -8x + 8x Combine like terms: -8x + 8x = 0 4 + 14x = -8 + 0 4 + 14x = -8 Add '-4' to each side of the equation. 4 + -4 + 14x = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 14x = -8 + -4 14x = -8 + -4 Combine like terms: -8 + -4 = -12 14x = -12 Divide each side by '14'. x = -0.8571428571 Simplifying x = -0.8571428571
| -14=5(a-5)+6(6a-5) | | 4(4x-3)-6=4x+2(3x-6) | | -3*n=30 | | 24=9z+6 | | 30x-4=x+6 | | 4(4x+3)-6=9x+12 | | 8+3x=6x-13 | | 2y=3x+14 | | 26=6(x+4)+2(1-8x) | | 11=-3x+20 | | h=14t | | 12m+2(7m-3)=46 | | 20=3r | | 12=5y-4 | | y=f(-x)+3 | | 15=-6(1+5v)+7(3-6V) | | 32=9a-4a | | 11p+16=-34-5 | | y=0.11x+18.34 | | 9c+3d= | | 0=-5t^2+23+10 | | -23=v-16 | | 8x-y=58 | | 6x+4=20-64 | | 13=13+n | | -k+78=98-20 | | 0.2X^2-3X+60=0 | | a-2=-6 | | -6z-20=4 | | 12x^2-128x-374=0 | | 5x+11=20x-4 | | 5(a-1)+6=-71 |